THE ROLE SHARIA PEER TO PEER LANDING SUPPORTS HALAL INDUSTRY - Trimulato, Trimulato; Mustamin, Asyraf; Syarifuddin, Syarifuddin (Asian Journal of Islamic Economic Studies, 2024)
The development of the Sharia financial industry is growing, and the types of products offered are increasingly varied and become people's choices, like present Sharia fintech. The Sharia financial industry is growing the halal industry too and gaining global recognition. Halal industry encouraged grow through access capital, and other support Islamic financial institutions. The role Sharia fintech can work to develop halal industry. Research purposes is to determine development the growth sharia fintech, and development halal industry. As well as outlining form of role sharia fintech supporting halal industry. Research methods are qualitative methods with library research. Secondary data sources are used, including the Financial Services Authority (OJK), National Committee Sharia Economics and Finance (KNEKS), LPPOM MUI, and other sources. The data collection technique used library-relevant sources and research theme. The analytical technique used is descriptive qualitative, describing the development, sharia fintech, the halal industry, and the role of sharia fintech in the halal industry. Sharia fintech Peer to Peer Landing (P2P) assets fell -12 percent, and players fell 12 percent. Certified halal products 2021 grew 2,531.49 percent. Spending on halal industry food sector is 77.23 total other halal industries. The role of Sharia fintech is to support the halal industry; funding business development is provided. The role sharia fintech synergize in assisting and marketing products for industry to get financing. Sharia fintech can synergize with assistance and product marketing for the halal industry to obtain financing. The role of sharia fintech in supporting the real sector, especially for the halal industry business with the service excellence it has.